Milk progesterone kits: On-farm use - Jeffrey S. Stevenson; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1986)
Diagnosing pregnancy in dairy cattle is an essential part of good management. The objective of this procedure is not to identify pregnant cows, but to identify the nonpregnant cows, those that become the breeding challenge. Economics dictate that verifying the pregnancy or "open" status of the cow is essential. Estimated losses of 1 to 3 per cow per day when conception is delayed beyond 85 days postpartum emphasize the importance of inseminating cows early to allow for 12 to 13-month calving intervals. A number of diagnostic tools are available and increasing scientific knowledge and technology will provide for improved pregnancy diagnosis in the future through use of cowside tests. These available procedures include: 1) continuous detection of estrus to identify inseminated cows that return to heat 18 to 24 days post breeding (repeat heats); 2) palpation of the uterus and its contents per rectum (sometime after day 35 of suspected pregnancy depending on the expertise of the clinician); 3) radioimmunoassays (RIA) of progesterone in milk, blood serum, and plasma; and 4) enzyme-linked immunoassays (ELISA) for progesterone in milk, blood serum, and plasma. At least five chemical cowside test kits are now available that use the ELISA-type tests for detecting progesterone in milk and one for blood serum in heifers (see reference 3).; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Milk progesterone kits; Corpus luteum; Estrous cycle